The Future of Constitutional Complaint in Indonesia: An Examination of Its Legal Certainty - Standy Wico; Michael Michael; Patricia Louise Sunarto; Anastasia Anastasia (Indonesian Journal of Law and Society, 2021)
To date, there is no trial mechanism for Indonesian citizens to claim their rights through the constitutional complaint, even if the Constitutional Court has existed since 2003. Consequently, there has been a mechanism for upholding and promoting constitutional rights, and it has been regarded to improve Indonesian democracy. Adhere to this view, in democratic states like Indonesia and Germany, constitutional rights are often ignored by the state, even though these rights are essential in the rule of law. This paper aimed to revisit the range of a constitutional complaint following its legal certainty wield to the Indonesian Constitutional Court. This paper used juridical research by examining legal principles, legal systematics, legal synchronization, legal history, legal theory, and using a comparative law approach. This paper showed that as the constitutional complaint different from judicial review, the adoption of this mechanism should be an alternative instead of an ultimate mechanism under the constitutional rights doctrine. To ensure legal certainty to a constitutional complaint, a legal basis was needed by regulating and applying it for actual implementation in society. Meanwhile, the Constitutional Court in adjudicating a constitutional complaint could be realized through the amendment of the 1945 Constitution. KEYWORDS: Constitutional Complaint, Constitutional Court, Indonesian Constitution.